Optimal Planning for Economic Stabilization: the application of control theory to stabilization policy - Pindyck, Robert S. (Amsterdam : North-Holland Publishing Company, 1973)
This book is the result of a doctoral thesis research of the author at the Massachusetts Institute of Technology. The perennial and often most controversial problems in economics have been to choose among alternative policies so as to best regulate or control the economy. Further more, the design of policies for economic stabilization is considerably complicated by the dynamic structure of the economic system.
Includes bibliographical references p. 161-164 and index.
hza 28/06/2018
Loans
Keywords: Economic stabilization; Control theory; United States